Hydrodynamic Response Analysis of a Fixed Aquaculture Platform with a Horizontal Cylindrical Cage in Combined Waves and Currents - Kanmin Shen; Chunwei Bi; Zhenqiang Jiang; Shouan Guo; Bin Wang (Journal of Marine Science and Engineering, 2023)
Biofouling on net cages adversely affects structural safety and the growth of aquacultural fish. Therefore, a novel fixed aquaculture platform with a rotatable horizontal cylindrical cage is proposed in this study, which is convenient for the cleaning of biofouling. Based on ANSYS, the numerical model of the fixed aquaculture platform was established. The response results of the strain, acceleration, and displacement of the structure under the combined action of waves and currents at three typical attack angles were calculated. The effects of water depth and cage rotation on the hydrodynamic response of the structure are discussed. The results show that the strain, acceleration, and displacement of the cage increase with the increase in wave height; however, the change with the wave period is not obvious. The direction perpendicular to the long axis of the cage is the most unfavorable load direction. The acceleration of each position increases with the increase in water depth; however, the strain response has the opposite trend. When the rotation constraint of the horizontal cylindrical cage is released, the acceleration of the cage is larger than that when the cage is fixed. The rotation of the cage has a tiny effect on the structural strain and load acting on the structure.